Implementation of IPv6 address generation mechanism for enterprise wireless local area network in open source DHCPv6 - Hakiem, Nashrul; Priantoro, Akhmad Unggul; Mutholib, Abdul; Siddiqi, Muhammad Umar; Hasan, Talib Hashim (2010)
This paper discusses the implementation of IPv6 address generation/assignment mechanism proposed in Dibbler DHCPv6. In the mechanism, each user is assigned with random address which uniquely allocated for his/her exclusive use. It is shown that it can be incorporated into existing Dibbler software and tested under various network topologies. The proposed mechanism will enhance user privacy by dynamic address assignment and yet does not compromise network visibility since users can be traced individually regardless of dynamically changing IPv6.